Temperature-reversible and washable shape memory adhesive material as well as preparation method and application thereof
By using crosslinked polymers of acrylate and polyurethane bisacrylate, a temperature reversible and cleanable shape memory adhesion material was prepared, which solved the problem of inconvenience in existing materials in applications and achieved the effect of multiple uses and accurate signal detection.
Patent Information
- Application Number
- CN202510082470.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-20
AI Technical Summary
Existing adhesive materials are difficult to achieve the comprehensive characteristics of reversible adhesion, washable and shape memory, resulting in inconvenient use in different application scenarios and may cause skin irritation or inaccurate sensor signals.
A crosslinked polymer with octadecyl acrylate, dodecyl acrylate and polyurethane diacrylate (UDA) as the main components is prepared by controlling the component ratio and ultraviolet light to initiate a polymerization reaction to prepare a temperature reversible and cleanable shape memory adhesive material.
The reversible adhesion characteristics of the material at different temperatures are achieved, with a cleanable surface, able to be reused, and providing accurate and timely detection of physiological signals in wearable strain sensors.
Smart Images

Figure CN119735753A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of adhesive material preparation, and in particular to a temperature-reversible and washable shape memory adhesive material and a preparation method and application thereof. Background Art
[0002] The adhesive layer of the flexible wearable device should have the characteristics of reversible adhesion because it needs to adhere to the skin, so as to adapt to different application scenarios. However, existing adhesive layers such as double-sided adhesive tape and self-adhesive silicone do not have the characteristics of reversible adhesion, and they need to be combined with the surface by means such as light pressure, which may often cause insufficient adhesion; and the removal of the adhesive layer may cause an inflammatory reaction, resulting in irritation or pain, further deepening the discomfort during use. At the same time, in the combined use of the adhesive layer and the microfluidic chip, the existing adhesive material cannot return to its original shape after deformation, and will mismatch with the liquid inlet channel of the microfluidic chip when used again. After repeated use, the surface of the adhesive layer will be contaminated with pollutants such as sweat stains and dust, thereby reducing or even losing the adhesion ability, and the adhesive layer cannot be effectively used multiple times. In addition, many existing wearable strain sensors adhere to human skin, and an additional adhesive layer needs to be added under the substrate, which may lead to inaccurate or untimely capture of many tiny physiological signals. Therefore, strain sensors prepared based on reversible adhesive materials have greater use value in practical applications. In order to solve these problems, the required adhesive material needs to have the characteristics of reversible adhesion, washability, shape memory and simple preparation process, so as to adapt to the use in different scenarios and improve the practicality and comfort of wearable devices. Summary of the invention
[0003] In view of the difficulties in the prior art that it is difficult to achieve reversible adhesion and a single material by simple means, and that it is impossible to have reversible adhesion, washability, and shape memory at the same time, the first purpose of the present invention is to provide a temperature-reversible and washable shape memory adhesive material. The adhesive material provided by the present invention has the characteristics of integrating temperature-reversible adhesion, washability, and shape memory, and has a reversible adhesion function due to its phase change characteristics: it is semi-crystalline below room temperature and the material exhibits non-stickiness; it is amorphous at skin temperature and exhibits strong adhesion, achieving temperature-reversible adhesion of the material; it has washable characteristics and can be cleaned after being contaminated with pollutants without affecting the adhesion of the material itself; it has shape memory characteristics and can be used as an adhesive patch to achieve reversible adhesion and reuse of adapted microfluidic chips.
[0004] The second object of the present invention is to provide a method for preparing a temperature-reversible and washable shape memory adhesive material. The preparation method of the present invention is prepared by a one-step method, and the preparation process is simple and controllable.
[0005] The third purpose of the present invention is to provide an application of a temperature-reversible and washable shape memory adhesive material, and the shape memory adhesive material is applied to a microfluidic chip as an adhesive patch to achieve reversible adhesion and repeated use; it is applied to a wearable flexible strain sensor, and since it can better adapt to the skin, the sensor can be used to detect small physiological signals of the human body, and the obtained signals are accurate and immediate.
[0006] In order to achieve the above object, the present invention adopts the following technical solution: The present invention discloses a temperature-reversible and washable shape memory adhesive material. The shape memory adhesive material is a cross-linked polymer of octadecyl acrylate, dodecyl acrylate and polyurethane diacrylate (UDA). In the shape memory adhesive material, the mass fraction of polyurethane diacrylate (UDA) is 15-25%, and the mass ratio of octadecyl acrylate to dodecyl acrylate is 1-1.75.
[0007] The shape memory adhesive material provided by the present invention is a cross-linked polymer of octadecyl acrylate and dodecyl acrylate. The present invention controls the ratio of octadecyl acrylate to dodecyl acrylate and utilizes dodecyl acrylate with a short alkyl side chain of 12 carbon atoms to reduce the phase change temperature of the adhesive material, so that the transition temperature of the adhesive material is slightly lower than the skin temperature. Since the material exhibits different states before and after the transition temperature: after being triggered by the skin temperature, the material changes from a semi-crystalline state to an amorphous state, and the film can easily flow and adhere to the target surface to form a smooth and tight fit that is difficult to peel off; and thereafter, when the surface temperature is lowered to room temperature, the film changes from an amorphous state to a semi-crystalline state, the adhesion strength is greatly reduced, and it is easy to debond; the material Reversible adhesion can be achieved at different temperatures, and the required temperature is within the safe range for the human body and is easy to achieve. In addition, the shape memory adhesive material provided by the present invention is a cross-linked polymer with a cross-linked network structure. Since the polymer molecular chain has good flexibility, the chain segments can rotate and move freely. Above the transition temperature, the material has high resilience, and the prepared adhesive patch has a shape memory function. In addition, due to the low adhesion at low temperatures and the adjustment of surface energy and roughness, the surface of the adhesive material has the property of being washable. After being stained with pollutants such as dust and sweat, the surface can be cleaned with water or alcohol, and the adhesion and shape memory properties of the material itself are not affected, and the material can be reused.
[0008] In the present invention, in order to simultaneously obtain the properties of reversible adhesion, washability, and shape memory, it is necessary to effectively control the raw materials and ingredients. If the proportion of dodecyl acrylate is too large, the phase transition temperature of the material will be too low, and the material will show amorphous adhesion properties at room temperature. If crystallization is required, the temperature must be lowered to a lower level; if the proportion of dodecyl acrylate is too small, the phase transition temperature of the material cannot be effectively reduced, and the prepared material must be at a higher temperature to show adhesion, and it is also brittle at room temperature and cannot be effectively used; and if dodecyl acrylate and polyurethane diacrylate are replaced with others, it may not be possible to simultaneously obtain reversible adhesion, washability, and shape memory, especially the characteristics of being able to be washed after being contaminated with pollutants without affecting the adhesion of the material.
[0009] Preferably, the phase change temperature of the shape memory adhesive material is 28-33°C.
[0010] The invention discloses a method for preparing a temperature-reversible and washable shape memory adhesive material. The method comprises the following steps: mixing octadecyl acrylate, dodecyl acrylate, polyurethane diacrylate (UDA), 2,2-dimethoxy-2-phenylacetophenone (DMPA) and benzophenone (Ben) to obtain a mixed solution, pouring the mixed solution into a mold and placing the mold on a hot stage, performing a cross-linking polymerization reaction initiated by ultraviolet light to obtain a cross-linked polymer containing an oligomer, heat-treating the cross-linked polymer containing the oligomer to remove the oligomer, and demolding the mold after refrigeration to obtain the adhesive material.
[0011] The preparation method of the present invention is prepared by a simple one-step process, using octadecyl acrylate and dodecyl acrylate as cross-linked polymer raw materials, UDA as a cross-linking agent, DMPA and Ben together as photoinitiators, pouring into a required mold and initiating free radical copolymerization through ultraviolet light of a specific wavelength, so as to prepare an adhesive material of a required shape in one step, and the triggering adhesion temperature is near human body temperature. The preparation method is simple and time-saving.
[0012] In the present invention, DMPA and Ben are used together as photoinitiators to improve the initiation efficiency, reduce the side reactions and the generation of oligomers, and increase the cross-linking degree, so that the obtained adhesive material has more excellent performance.
[0013] In a preferred embodiment, the mass ratio of octadecyl acrylate to dodecyl acrylate is 1 to 1.75.
[0014] In a preferred embodiment, the amount of UDA added is 15-25% of the total mass of octadecyl acrylate and dodecyl acrylate.
[0015] In a preferred embodiment, the mass fraction of DMPA in the mixed solution is 0.5-1%, and the mass fraction of Ben in the mixed solution is 0.2-0.5%.
[0016] In a preferred embodiment, the mixing method is ultrasonic dispersion, the ultrasonic dispersion time is 30 to 60 minutes, and the ultrasonic dispersion temperature is 50 to 60°C.
[0017] In actual operation, CO2 laser cutting technology can be used to prepare silicone molds of appropriate sizes.
[0018] In a preferred embodiment, when preparing a patterned shape memory adhesive material, the preparation process of the mold is: using a CO2 laser to cut a silicone pad to prepare the grooves of the desired pattern to obtain a silicone pad A containing a pattern, and then placing a silicone pad B of the same size as the silicone pad A under the silicone pad A as a bottom surface to assemble the mold. In a preferred embodiment of the present invention, the mold is prepared by CO2 laser cutting technology, and the shape and thickness are easy to control. The mixed solution is poured into the mold for one-step preparation to obtain an adhesive patch that can be used for adhesion to a variety of surfaces, such as materials that can be used for adhesion to different surfaces including rough and smooth.
[0019] In a preferred solution, the temperature of the hot stage is 50-60° C. At the above temperature, ultraviolet light initiation can ensure that the ambient temperature is above the melting point of all raw materials during preparation, avoiding the influence of temperature on the degree of reaction, thereby obtaining an adhesive material with excellent performance.
[0020] In a preferred embodiment, when the ultraviolet light is used for initiation, the wavelength of the ultraviolet light used is 365 nm.
[0021] Preferably, the cross-linking polymerization reaction time is 15 to 25 minutes.
[0022] In a preferred embodiment, the heat treatment temperature is 60-70°C and the heat treatment time is 2-3 hours. The oligomers are removed by placing the cross-linked polymer containing oligomers in an environment above the melting point for 2-3 hours to avoid residues on the skin surface during subsequent use.
[0023] The shape memory adhesive material provided by the present invention can be used for the adhesion of various materials, such as PET, metal, 3D printing resin, glass sheet, filter paper, silicone, etc., and has strong adhesion. Based on this, the material can replace double-sided tape and self-adhesive silicone as an adhesive patch for many flexible devices to reversibly adhere to the skin. Since it also has washable and shape memory properties, the adhesive patch can be reused.
[0024] The present invention also provides an application of a temperature-reversible and washable shape memory adhesive material, wherein the shape memory adhesive material is used as an adhesive patch in a soft-hard combination-detachable microfluidic device.
[0025] Since the shape memory adhesive material provided by the present invention has strong adhesion to different surfaces, it can replace double-sided tape as an adhesive patch for the application of reversible adhesion of soft-hard combined-detachable microfluidic devices to the skin.
[0026] When using, first use 3D drawing software to draw a microfluidic chip that can collect and store sweat, and then use a 3D printer to print it. After the chip is cleaned, the hard part of the soft-hard combination-detachable microfluidic device can be obtained, and the whole part is a hydrophilic material. When the temperature is above the skin temperature, the soft adhesive patch and the hard part can be tightly combined, and the soft part can be tightly adhered to the skin; at the same time, due to the characteristics of the material itself, when the microfluidic device is on the skin, sweat will be transported to the hard part from the hole channel reserved between the adhesive patches due to capillary force, so that sweat can be easily collected and stored for in vitro testing; after use, it is placed in an environment below the skin temperature, and the adhesive patch can be debonded from the skin, and the place where it adheres to the skin is debonded before the place where it adheres to the device, which can maintain the integrity of the device and the soft and hard parts can be disassembled.
[0027] In addition, since the material has strong shape memory and washable properties, the prepared adhesive patch can be cleaned and dried above the melting point of the material after disassembly, so that an adhesive patch that maintains the original shape and is clean and tidy can be obtained. Therefore, it can be used repeatedly. The shape memory property can protect the microfluidic channels reserved in the adhesive patch. Compared with other commonly used adhesive materials at this stage that cannot be reversibly adhered and can only be used once, this material shows a very great advantage.
[0028] The main body of the microfluidic device is a hard part printed by 3D modeling, and its shape and size are controlled by the system. There is little difference between devices and the chip can be used multiple times.
[0029] The microfluidic device can carry out directional transport and collection of sweat, has a simple preparation process, and the directional transport characteristics are determined by the material itself, without the need for additional hydrophilic treatment.
[0030] The microfluidic device is detachable and can be used for in vitro sweat analysis and detection.
[0031] The adhesive patch has shape memory characteristics, avoids the problem of mismatch with the microfluidic channel, and can be reused after being disassembled.
[0032] The adhesive patch has a washable property and can be easily washed with water or alcohol even if it is stained, without affecting the adhesion of the material itself.
[0033] The present invention discloses an application of a temperature-reversible and washable shape memory adhesive material, and applies the shape memory adhesive material to a wearable flexible strain sensor. A super-hydrophobic conductive layer is constructed on the surface of the adhesive material using a "glue + powder" method to prepare a wearable flexible strain sensor. Since the sensor can better adapt to the skin, the sensor can be used to detect small physiological signals of the human body, and the obtained signals are accurate and immediate.
[0034] According to a preferred embodiment, the preparation process of the wearable flexible strain sensor is as follows: spin coating the Ecoflex solution on the surface of the shape memory adhesive material to form a glue layer, compounding multi-walled carbon nanotubes (CNTs) in the glue layer to form a super-hydrophobic conductive layer; finally, preparing a conductive electrode on the surface of the super-hydrophobic conductive layer, and then welding the conductive electrode to a wire.
[0035] Further preferably, the Ecoflex solution is evenly spin-coated on the surface of the shape memory adhesive material at a rotation speed of 1500 rpm to 2000 rpm for 20 to 40 seconds to form a glue layer.
[0036] Further preferably, the CNTs are compounded with the glue in the glue layer by a rod coating method and thermally cured at 60-70° C. for 2-3 hours to form a super-hydrophobic conductive layer.
[0037] When applying shape memory adhesive materials to wearable flexible strain sensors, firstly, a silicone mold of suitable size is prepared by CO2 laser cutting technology, and the adhesive material is prepared and used as the base of the strain sensor; secondly, a glue spreader is used to evenly spin-coat the surface of the adhesive material with the configured Ecoflex solution at a speed of 1500rpm~2000rpm for 20~40s to form a "glue" layer, and multi-walled carbon nanotubes (CNTs) are selected as the conductive medium, and the super-hydrophobic conductive layer is prepared by the "glue-powder" method; finally, conductive electrodes are constructed on the conductive layer and the wires are welded to obtain a flexible wearable strain sensor that can be used to monitor human physiological signals. Its bottom surface has the characteristics of reversible adhesion and perfect adaptation to the skin. The device can be used to monitor subtle physiological signals of the human body, and the signals obtained are accurate and immediate.
[0038] The sensor provided by the present invention does not require an additional adhesion layer and has temperature-reversible adhesion characteristics. The size of the sensor can be prepared by mold cutting as needed. The sensor adhesion layer is the substrate, and the signal transmission is more accurate; the conductive layer is prepared by the "glue-powder" method, and the prepared composite material has both conductive and super-hydrophobic properties; the conductive medium is CNTs, and due to the aspect ratio of the material itself, when used as a structureless strain sensor, the composite conductive layer has a linear response characteristic.
[0039] The beneficial effects of the present invention are as follows: 1. The present invention prepares a temperature-reversible and washable shape memory adhesive material by initiating free radical polymerization with ultraviolet light of a specific wavelength. The material has a simple preparation process and excellent performance.
[0040] 2. The adhesive material of the present invention can be used to adhere to a variety of surfaces including rough and smooth surfaces.
[0041] 3. The present invention provides a process for preparing a soft-hard combined and reversibly disassembled microfluidic device, and the collected sweat can be used for in vitro detection.
[0042] 4. The present invention provides a strain sensor that does not require an additional adhesive layer and can be reversibly adhered to the skin. It can better adapt to the skin and the measured signal is more immediate and accurate. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 Schematic diagram of the process of reversible adhesion of the adhesive material prepared in Example 1 on the skin (left figure) and the adhesion strength test cycle data curve under the corresponding state (right figure): after the prepared adhesive material is placed on the skin, the material is transformed into an amorphous state, can fit the skin perfectly, adapt to various deformations and will not debond, but when the temperature is lowered, the material crystallizes, the adhesion force is greatly reduced, and it is easy to debond; the adhesion strength test at different temperatures also shows the reversible adhesion characteristics of the material, and it still has a high adhesion strength after multiple cycles.
[0044] Figure 2 This is a data analysis diagram showing the principle of reversible adhesion of the adhesive material prepared in Example 1, including a dynamic modulus test (left figure) and a phase change temperature test curve (right figure): The corresponding data also show that the adhesion properties of the adhesive material at different temperatures are due to the different forms of the material deformed before and after the transition temperature: a semi-crystalline state and an amorphous state. By regulating the crystallization temperature, the appropriate range of the mass ratio of SA to DA is determined.
[0045] Figure 3 The shape memory process of the adhesive material prepared in Example 1 (left figure) and the material recovery rate data curve under multiple cycles (right figure): The adhesive material has good shape memory properties, and even after 100 cycles of stretching, the material still has high recovery.
[0046] Figure 4 This is a real picture of the adhesive material prepared in Example 1 that can be cleaned after being contaminated with pollutants, wherein the left picture is before cleaning and the right picture is after cleaning, indicating that after its surface is contaminated with pollutants such as sweat stains, dust, etc., it can be cleaned with water or alcohol without affecting the adhesion and other properties of the material.
[0047] Figure 5 These are pictures showing the effects of the adhesive patch prepared in Example 2 being adhered to the surfaces of various materials.
[0048] Figure 6 Schematic diagram of the structure of the 3D printed hard microfluidic chip in Example 3, which includes a sweat inlet, a liquid inlet channel and a sweat collection chamber.
[0049] Figure 7 The performance characterization diagram of the super-hydrophobic conductive layer prepared by the "glue + powder" method in Example 4, including the conductive performance (left figure) and the surface contact angle test (right figure), both of which indicate the successful preparation of the super-hydrophobic composite conductive layer. DETAILED DESCRIPTION
[0050] The present invention is described in detail through the following specific embodiments, but it is obvious that the protection scope of the present invention is not limited to these embodiments.
[0051] Example 1 This example is used to illustrate a method for preparing a temperature-reversible and washable shape memory adhesive material in the present invention. Figure 1 As shown, it includes the following steps: 1) octadecyl acrylate (SA) and dodecyl acrylate (DA) were weighed in a mass ratio of 3:2 and placed in a beaker, and a crosslinker UDA was added thereto at 20% of the total mass, and a photoinitiator was added at a ratio of 1% DMPA and 0.5% Ben by total weight; 2) Heat the ultrasonic machine to 50°C and place the beaker in it for 30 minutes to allow the raw material components to be fully mixed; 3) Pour the dispersed mixed solution into the mold and place it on a 50°C hot plate to maintain a reaction environment above the melting point of the raw materials; 4) Use ultraviolet light with a specific wavelength of -365nm to initiate photopolymerization for 20 minutes, place it at 60°C for 2 hours to remove oligomers, and then place it in a refrigerator for refrigeration and demoulding to obtain the desired adhesive material.
[0052] In addition, with other conditions being the same as above, adhesive materials with mass ratios of SA to DA of 1:4, 1:1, 3:2, 9:2, and 5:0 were prepared.
[0053] Figure 1 The process diagram of the reversible adhesion of the adhesive material on the skin prepared in Example 1 and the cyclic data curve of the adhesion strength test under the corresponding state are shown in the diagram on the left. From the diagram on the left, it can be seen that after the adhesive material is placed on the skin, the material changes to an amorphous state, can fit the skin perfectly, adapt to various deformations and will not debond, but when the temperature is lowered, the material crystallizes, the adhesion is greatly reduced, and it is easy to debond; from the right figure, the adhesion strength tests conducted at 36°C and 20°C respectively also show the reversible adhesion characteristics of the material, and it still has a high adhesion strength after multiple cycles.
[0054] Figure 2 This is a data analysis diagram showing the principle of reversible adhesion of the adhesive material prepared in Example 1, including a dynamic modulus test (left figure) and a phase change temperature test curve (right figure): The corresponding data also show that the adhesion properties of the adhesive material at different temperatures are due to the different forms of the material deformed before and after the transition temperature: a semi-crystalline state and an amorphous state. By regulating the crystallization temperature, the appropriate range of the mass ratio of SA to DA is determined.
[0055] Figure 3 This is the shape memory process of the adhesive material prepared in Example 1 (left figure) and the material recovery rate data curve under multiple cycles (right figure): It can be seen from the right figure that even after 100 cycles of stretching, the material still has high recovery.
[0056] Figure 4 This is a real picture of the adhesive material prepared in Example 1 that can be cleaned after being contaminated with pollutants, wherein the left picture is before cleaning and the right picture is after cleaning, indicating that after its surface is contaminated with pollutants such as sweat stains, dust, etc., it can be cleaned with water or alcohol without affecting the adhesion and other properties of the material.
[0057] Example 2 This example is used to illustrate the preparation process of the adhesive patch in the present invention, which includes the following steps: 1) Use Auto-CAD to draw the pattern according to the required shape and import it into the CO2 laser cutting machine. After removing the adhesive on the surface of the silicone pad, place it in the corresponding position for laser cutting to obtain a hollow silicone pad with the required pattern. After cleaning it, place a cleaned silicone pad of the same size underneath it to assemble the mold with the required pattern; 2) Fix the silicone pad mold on a glass sheet and place it on a 50°C hot plate, pour the prepared mixed solution into it, use photo-initiated polymerization and post-processing to obtain an adhesive patch with the desired pattern.
[0058] Figure 5 These are pictures showing the effects of the adhesive patch prepared in Example 2 being adhered to the surfaces of various materials.
[0059] Example 3 This example is used to illustrate the preparation process of the adhesive material used for the soft-hard combination-detachable microfluidic chip in the present invention, which includes the following steps: 1) Use 3D drawing software such as SolidWorks to draw a microfluidic chip model including channels and collection chambers, slice the model with dedicated software and import it into a 3D printer for printing (the 3D printing resin used is a light-cured water-washable resin). After printing, disassemble and clean it to obtain the required hard parts; Figure 6The schematic diagram of the structure of the hard microfluidic chip shown in the figure includes a sweat inlet, a liquid inlet channel and a sweat collection chamber; 2) Pour the prepared mixed solution into the desired pattern silicone pad mold and perform photoinitiated polymerization to obtain an adhesive patch; 3) Assembling the adhesive patch with the hard layer can obtain a soft-hard combined-detachable microfluidic device; 4) The device can be attached to the skin to collect sweat. The chip is reversibly adhered, and its soft and hard parts are detachable. The collected sweat can be used for in vitro testing.
[0060] Example 4 This example is used to illustrate the preparation method of the wearable strain sensor in the present invention: 1) First, a silicone pad mold with a size of 30×5×0.5 mm was prepared by a CO2 laser cutting machine; 2) preparing a mixed solution of adhesive material and an Ecoflex solution with a mass ratio of A:B components of 1:1; 3) using a mold to prepare a substrate with reversible adhesion properties having a size of 30×5×0.5 mm; 4) Spin coat the Ecoflex solution on the substrate at 2000 rpm for 30 seconds using a coating machine to prepare a "glue" layer; 5) CNTs and "glue" were compounded by rod coating method and thermally cured at 60°C for 2h to obtain a super-hydrophobic conductive composite layer; 6) using conductive silicone and copper foil to prepare electrodes on the surface of the super-hydrophobic conductive layer, and then heat-curing at 80° C. for 4 h to connect the wires using a welding process; 7) To prevent the electrode from short-circuiting or other failures due to water, the electrode part is treated with super-hydrophobic treatment using potting glue and thermally cured for 2 hours to obtain a wearable strain sensor integrating reversible adhesion and super-hydrophobicity.
[0061] Figure 7 The performance characterization diagram of the super-hydrophobic conductive layer prepared by the "glue + powder" method in Example 4, including the conductive performance (left figure) and the surface contact angle test (right figure), both of which indicate the successful preparation of the super-hydrophobic composite conductive layer.
[0062] The sensor can adhere to the skin by itself without the need for an additional adhesive layer. The measured data is more accurate and timely, and is easier to use for real-time monitoring of human movement.
Claims
1. A temperature-reversible and washable shape memory adhesive material, characterized in that: The shape memory adhesive material is a cross-linked polymer of octadecyl acrylate, dodecyl acrylate and UDA. In the shape memory adhesive material, the mass fraction of UDA is 15-25%, and the mass ratio of octadecyl acrylate to dodecyl acrylate is 1-1.
75.
2. The temperature-reversible and washable shape memory adhesive material according to claim 1, characterized in that: The phase transition temperature of the shape memory adhesive material is 28-33°C.
3. The method for preparing a temperature-reversible and washable shape memory adhesive material according to claim 1 or 2, characterized in that: Octadecanyl acrylate, dodecyl acrylate, UDA, DMPA and Ben are mixed to obtain a mixed solution, the mixed solution is poured into a mold and placed on a hot stage, a cross-linking polymerization reaction is initiated by ultraviolet light to obtain a cross-linked polymer containing oligomers, the cross-linked polymer containing oligomers is heat-treated to remove the oligomers, and the adhesive material is obtained by demolding after refrigeration.
4. The method for preparing a temperature-reversible and washable shape memory adhesive material according to claim 3, characterized in that: The mass ratio of octadecyl acrylate to dodecyl acrylate is 1 to 1.75; The amount of UDA added is 15-25% of the total mass of octadecyl acrylate and dodecyl acrylate; The mass fraction of DMPA in the mixed solution is 0.5-1%, and the mass fraction of Ben in the mixed solution is 0.2-0.5%; The mixing method is ultrasonic dispersion, the ultrasonic dispersion time is 30-60 minutes, and the ultrasonic dispersion temperature is 50-60°C.
5. The method for preparing a temperature-reversible and washable shape memory adhesive material according to claim 3, characterized in that: When preparing a patterned shape memory adhesive material, the preparation process of the mold is as follows: CO2 laser cuts the silicone pad to prepare the required patterned groove to obtain the patterned silicone pad A, and then places a silicone pad B of the same size as silicone pad A under the silicone pad A as the bottom surface to assemble the mold.
6. The method for preparing a temperature-reversible and washable shape memory adhesive material according to claim 3, characterized in that: The temperature of the hot stage is 50-60°C; When the ultraviolet light is used for initiation, the wavelength of the ultraviolet light used is 365nm; The cross-linking polymerization reaction time is 15 to 25 minutes.
7. The method for preparing a temperature-reversible and washable shape memory adhesive material according to claim 3, characterized in that: The temperature of the heat treatment is 60-70° C., and the time of the heat treatment is 2-3 hours.
8. The use of a temperature-reversible and washable shape memory adhesive material according to claim 1, characterized in that: The shape memory adhesive material is used as an adhesive patch in a soft-hard combination-detachable microfluidic device.
9. The use of a temperature-reversible and washable shape memory adhesive material according to claim 1, characterized in that: The shape memory adhesive material is applied to wearable flexible strain sensors.
10. The use of a temperature-reversible and washable shape memory adhesive material according to claim 9, characterized in that: The preparation process of the wearable flexible strain sensor is as follows: spin coating the Ecoflex solution on the surface of the shape memory adhesive material to form a glue layer, compounding the multi-walled carbon nanotubes in the glue layer to form a super-hydrophobic conductive layer; finally, preparing a conductive electrode on the surface of the super-hydrophobic conductive layer, and then welding the conductive electrode to a wire; The Ecoflex solution is evenly spin-coated on the surface of the shape memory adhesive material at a rotation speed of 1500 rpm to 2000 rpm for 20 to 40 seconds to form a glue layer; The CNTs were compounded with the glue in the glue layer by a rod coating method and thermally cured at 60-70°C for 2-3h to form a super-hydrophobic conductive layer.
Citation Information
Patent Citations
Application method and preparation method of octadecyl acrylate homopolymer shape memory material, and medical fracture fixation device
CN103751855A
Thermoregulable shape memory polymer material and preparation method thereof
CN107011647A
Temperature-controlled self-adhesive conductive composite material based on shape memory effect as well as preparation method and application thereof
CN112538327A
Color-changing dielectric elastomer material as well as preparation method and application thereof
CN116693766A
Shape-memory resin, and molded body using this
JP2008121004A
Cited By
Reversible adhesive flexible semiconductor refrigeration device and preparation method and application thereof
CN121442944A
Reversible adhesive flexible semiconductor refrigeration device and preparation method and application thereof
CN121442944B